Systematic Literature Review: Kesulitan Belajar Mahasiswa Pendidikan Matematika - Hikmah Fazariah; Rusi Ulfa Hasanah; Reni Purnama Sari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mathematics education student learning difficultis ar influenced bye several factors, both internal ands external. This research aims to identify and analyze they learning difficulties experienced by mathematics education study program students. The methods used as Systematic Literature Review (SLR) bye collecting and analyzis scientific articles related to student learning difficulties published in the last 10 years.